Opportunities to reduce the risk of stroke in AF: the REVIEW AF study. (25th November 2020) - Gallagher, C; Wong, C.X; Hendriks, J.M; Nyfort-Hansen, K; Rowett, D; Bednarz, J; Elliott, A.D; Linz, D; Middeldorp, M.E; Mahajan, R; Lau, D.H; Sanders, P
Abstract: Background: Stroke is one of the most devastating complications of atrial fibrillation (AF) and is associated with poor patient outcomes. Recent registry data has demonstrated improved use of stroke prevention therapy with the advent of direct-acting oral anticoagulants, but little data exists in the Australian health care setting. Purpose: To examine the use of oral anticoagulant therapy in a cohort of individuals presenting to the emergency department (ED) due to AF. Methods: A total of 437 consecutive individuals who presented to the ED with a primary diagnosis of AF to three tertiary hospitals in our city in South Australia between March 2013 and March 2014 were included. Data were collected retrospectively from electronic medical record review. CHA2DS2-VASc and HAS-BLED scores were calculated and any documented contraindications to the use of oral anticoagulation (OAC) taken in to consideration. Results: Mean age was 69±15 years and 49.9% were male. A total of 244 (55.8%) individuals had a prior diagnosis of AF at index presentation. 179 (73.4%) of these individuals recorded a CHA2DS2-VASc score of ≥2. A total of 124 of these individuals were appropriately anticoagulated (69.3%) whilst 37 individuals were not treated with OAC and did not have a documented contraindication (20.7%). Anticoagulation status was unknown in 18 individuals due to a lack of documentation (10.0%). A CHA2DS2-VASc score of 0 was recorded in 25 individuals with a prior diagnosis of AF at index presentation with 3 individuals (12%) inappropriately overtreated with OAC. The remaining 193 individuals (44.2%) presented with a first episode of AF. In 129 (66.8%) of these individuals a CHA2DS2-VASc score of ≥2 was recorded and only 10 individuals had a documented contraindication to the use of OAC. In 119 (61.7%) individuals there were no documented contraindications to the use of OAC. In 74 (62.2%) of these presentations OAC was not commenced, whilst in 45 (37.8%) individuals OAC was prescribed. Conclusions: Significant opportunity exists to improve the use of stroke prevention therapy in AF. Despite repeated opportunities to commence this therapy within the hospital setting, it remains frequently underutilised in individuals at high risk of stroke. Funding Acknowledgement: Type of funding source: None